Nurses’ compliance with infection control, safety measures, communication, and protocol adherence in operating rooms of governmental hospitals in the Gaza strip - Abu Rahmah, Mohammed A.; ELssyed Etewa, Bothyna B.; Al’Haj Ahmad, Fatma; El Bilbeisi, Abdel Hamid (Frontiers in Health Services, 2025)
BackgroundThis study assessed nurses’ compliance with infection control, safety measures, communication, and protocol adherence in operating rooms of government hospitals in Gaza.MethodsA cross-sectional study was conducted in 2023 across the three main governmental hospitals in Gaza: Al Shifa Medical Complex, Nasser Medical Complex, and Gaza European Hospital. A census sampling method included 150 nurses working in operating rooms who met inclusion criteria. Data were collected using a structured, validated questionnaire covering demographics and six domains of patient safety based on the WHO Patient Safety Assessment Tool. Statistical analysis was performed using SPSS version 26, with significance set at p-value < 0.05.ResultsAmong 150 nurses (78% male, mean age 32.94 ± 7.3 years); most (71.4%) held a bachelor’s degree; and 43.3% had specialized operating room training. Positive responses on sterilization and cleaning averaged 46.7%, highest at Al Shifa (51.8%). Key practices such as instrument transport in sealed trolleys (80.7%) and immediate cleaning post-procedure (83.3%) were well reported. Intraoperative precaution compliance was 73.3%, with high rates of proper hand scrubbing (84.7%) but lower adherence to checklist completion (65.3%). Immediate post-operative monitoring adherence was 68.7%, with oxygen saturation measurement (88%) and pain assessment (77.3%) rated highly. Communication satisfaction was 72.7%, though cooperation during patient positioning was only 46%. About 66.7% reported positive views on policies and training, yet 75.3% expressed a need for more patient safety education. A high incidence of adverse events was reported by 93.3%, with reluctance to document errors noted by 68%.ConclusionThis study highlights moderate compliance with infection control in Gaza Strip operating rooms but reveals significant gaps in protocol adherence, documentation, and error reporting. It highlights the need for better training, resource support, and a non-punitive safety culture. Policymakers and hospital leaders must prioritize these to improve surgical safety and patient care.